Juridical Analysis Of Handling Optimization Election Crimes At The Gakkumdu Center: Research Study On Bawaslu Batam City - Ervin Fitianingrum; Ramlan Ramlan; Lagat Parroha Patar Siadari; Soerya Respationo; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The handling of election crimes is one of the important aspects in maintaining the integrity and fairness of the process of holding general elections in Indonesia. The Integrated Law Enforcement Center (Gakkumdu Center) was formed as a forum for law enforcement of violations of crimes in General Rehabilitation which is carried out in an integrated manner by Bawaslu, the National Police, and the Prosecutor's Office. However, in practice, in the Batam City Gakkumdu Center, it was found that there were obstacles caused by Batam City Gakkumdu Center officers who did not understand their duties and authorities as well as the applicable rules in handling election violation cases, namely investigators who did not carry out investigations in the Gakkumdu Center. This study aims to analyze juridically the optimization of the handling of election crimes by the Gakkumdu Center with a focus on the Batam City Bawaslu. This study uses a normative juridical research method with a qualitative approach. Data was collected through document studies, in-depth interviews with members of Bawaslu, the Police, and the Prosecutor's Office, as well as direct observation of the case handling process by the Gakkumdu Center in Batam City. Data analysis is carried out in a descriptive-analytical manner to identify obstacles and formulate optimization efforts. The results of the study show that there are officers of the Batam City Gakkumdu Center who are not compliant in carrying out their duties and authorities in accordance with applicable rules in handling cases of election violations, namely investigators who do not carry out investigations in the Gakkumdu Center so that as a result of Bawaslu members at the Gakkumdu Center being confused/not taking a stand in deciding the case to be stopped/continued because the facts of the calrification results are not drawn optimally, so that there is a potential for expiration in case handling and administrative issuance that does not comply with principles. This study concludes that optimizing the handling of election crimes at the Gakkumdu Center in Batam City requires a comprehensive and integrated approach. By implementing the recommended steps, it is hoped that the Gakkumdu Center in general can be more effective and procedural in carrying out its duties so that the law enforcement